Analisis Persepsi Pengunjung Terhadap Ketersediaan Produk Wisata Di Pantai Sauwmyen Distrik Oransbari Kabupaten Manokwari Selatan - Bartolomeus Kawey; Rumas Alma Yap; Naftali Mansim (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
Tourism products are an important part of the development of tourism sector. the real conditions of tourism products in the form of tourist attractions, facilities, at the location of the tourism attraction at the Sauwmyen beach re not very supportive for tourist activity. this condition will certainly greatly affect the experience and comfort travel. This study aims to determine the perceptions of tourists about the condition of tourism products and the comfort of tourist visitors obtained during a trip to Sauwmyen Beach, Oransbari district, South Manokwari Regency. Frequency distribution analysis technique, Customer Satisfaction Index (CSI) and the IPA (Import and Performance Analysis) approach were used as analysis methods. Result showed that the availability of tourism product in the form of tourism attraction excitability and adequate facilities are not fully found at the location of tourist object, there for their result of data analysis show that respondents’ perceptions of tourism product at tourist object are less satisfied. Then according to reality then the comfort of tourist visitors while in tourist sites is less satisfied. Then the strategy is the need for the development of sauwmyen beach tourism object by local residents and the government to improve performance, indicator tourism product that have a primary need for visitors and can be seen in the respondents of each individual in terms of their interest and performance for the development of a better Sauwmyen beach tourism object in the future to be used by all tourists.